MOLECULAR DETECTION OF PROSTATE CANCER USING A PANEL OF DNA METHYLATION BIOMARKERS - Dumache Raluca; Puiu Maria; David Dana; Negru Serban; Dumitrascu Victor (European Scientific Journal, ESJ, 2013)
Introduction: The diagnostic of prostate cancer (PCa) using serumbasedprostate specific antigen (PSA) has some limitations due to falsepositiveand negative results. The purpose of our study was to analyse thehypermethylation of three genes from plasma samples and to determine the feasibility of these genes to aid as biomarkers in detecting PCa in plasma by noninvasive methods.Materials and Methods: Genomic DNA was extracted from the peripheralblood plasma of 74 patients with localized PCa. All the samples wereexamined for aberrant hypermethylation in retinoic acid receptor β variant 2 (RARβ2), glutathione S-transferase P1 (GSTP1) and Ras association domain family 1 isoform A(RASSF1A) genes, using methylation-specific PCR (MSP), and the results were correlated with the clinicopathologicalparameters.Results: The percent of methylation of the analyzed genes was as follows: RARβ2 was found methylated in 54 cases (73 %), GSTP1 in 58 cases (78.4%), and RASSF1A was found methylated in all 74 cases (100%).Conclusion: Our study demonstrates that, using a panel of DNA methylated biomarkers aids the identification of PCa patients and with minimally invasive techniques , may yield information independent of serum PSA or the TNM stage.